The Effect of Live Streaming Commerce on Electronic Word-of-Mouth Mediated by Brand Image: A Study Among Digital Fashion Consumers in Jakarta - Budiman, Muhammad Fatiha Rizki; Rufaidah, Popy (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of live streaming commerce on electronic word-of-mouth with brand image as a mediating variable among young consumers in Jakarta. The study focuses on the local fashion industry, with local fashion industry the research object. The research employed a quantitative approach with an explanatory design, using a survey method involving 435 respondents who have watched live streaming commerce on various e-commerce platforms. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through the SmartPLS 4 software. The results show that live streaming commerce has a positive and significant effect on brand image as well as on electronic word-of-mouth. In addition, brand image also has a positive and significant influence on electronic word-of-mouth. The mediation analysis indicates that brand image partially mediates the relationship between live streaming commerce and electronic word-of-mouth. These findings reveal that interactive experiences in live streaming commerce can strengthen brand perception among young consumers, which in turn encourages them to share positive experiences and product recommendations online. Overall, the results of this study emphasize the important role of brand image in strengthening the impact of live streaming commerce strategies on young consumers’ communication behavior in the digital era. These findings provide practical implications for e-commerce practitioners and local fashion brands to optimize live streaming as an effective interactive promotional medium for building brand image and enhancing electronic word-of-mouth organically.